Terapi Walking Exercise (Jalan Kaki) Bagi Penderita Diabetes Mellitus Di Desa Naga Timbul Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2023 - Kamaliah Ainun; Muslimah Pase; Kristina Kristina; Helen Milianti (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to evaluate the effectiveness of walking therapy for Diabetes Mellitus patients in Naga Timbul Village, Tanjung Morawa District, Deli Serdang Regency, in 2023. The research method used is an intervention study with a pre-post design. The sample of this research is 50 randomly selected Diabetes Mellitus patients. They participated in a walking therapy program for 12 weeks with a frequency of three times a week. The results of the study showed a significant decrease in fasting blood sugar levels and HbA1c in participants after undergoing the walking therapy program. Additionally, there was a significant improvement in physical ability and psychological well-being of the participants. No significant side effects were reported by participants during the therapy program. This research concludes that walking therapy is effective in managing blood sugar levels and improving overall health in Diabetes Mellitus patients in Naga Timbul Village. This program can be considered as a safe and affordable alternative therapy for diabetes mellitus management, especially in rural areas.